2018
DOI: 10.1002/icd.2090
|View full text |Cite
|
Sign up to set email alerts
|

Developing theory of mind abilities in Swedish pre‐schoolers

Abstract: This study explored the development of theory of mind (ToM) in 80 Swedish-speaking 3-to 5-year-olds, a previously unstudied language and culture. The ToM scale was translated and tested in a Swedish context. The results show that the ToM abilities improve significantly with age. In addition, a gender difference was observed for the whole sample, girls outperformed boys, but follow-up analyses revealed that the difference only remained significant for the 4year-olds. No gender differences were observed at 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Extant conceptions of ToM development have also assumed similarity across ages. This is evidenced by studies generally taking preschoolers as a single age group in order to find the most prevalent pattern (see for an exception, Sundqvist et al, 2018). Moreover, performance differences have been generally attributed to a variable (i.e., cultural attitudes) that either was not measured (e.g., Wellman et al, 2006); when measured, did not reveal the expected differences (e.g., Kabha & Berger, 2020); or was measured with a proxy variable that showed the opposite of the expected results (Selcuk et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant conceptions of ToM development have also assumed similarity across ages. This is evidenced by studies generally taking preschoolers as a single age group in order to find the most prevalent pattern (see for an exception, Sundqvist et al, 2018). Moreover, performance differences have been generally attributed to a variable (i.e., cultural attitudes) that either was not measured (e.g., Wellman et al, 2006); when measured, did not reveal the expected differences (e.g., Kabha & Berger, 2020); or was measured with a proxy variable that showed the opposite of the expected results (Selcuk et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that in contrast to the other tasks in the scale, there was no age difference for DD or DB performance. Given that previous studies have not reported task performance by age (for an exception, see Sundqvist et al, 2018), it is impossible to know whether such stagnation is covertly present in the literature. The developmental stagnation present in the current data may not constitute a major problem for the DD task, where the results are comparable to other work.…”
Section: What If the Multiplicity Of Sequences Is The Norm Across Cul...mentioning
confidence: 99%
“…Refined aspects of shared intentionality such as the understanding of other's beliefs and emotions are a result not only of individual cognition but of profound experiences of interaction, in particular linguistic interaction, and of participation in reflective discourse (e.g., Tomasello, 2018;Tomasello & Rakoczy, 2003). Children generally pass traditional false belief tasks at approximately age 4 (e.g., Sundqvist et al, 2018;Tomasello, 2018;Wellman et al, 2001. Such tests are usually set up so that children are explicitly asked to make conclusions regarding a fictional character's (false) belief, thus bearing strong similarities to explaining a false belief in a story setting.…”
Section: Social Cognitionmentioning
confidence: 99%
“…Girls may show an advantage in the ability to ascribe mental states to story characters, which could be based on stronger ToM, superior language skills, and/ or better EF. Girls have been shown to outperform boys on false belief tasks in several studies (Calero et al, 2013;Charman et al, 2002;Frank et al, 2015;Sundqvist et al, 2018;Walker, 2005). Regarding Swedish children, girls have superior general language skills compared to boys (e.g., Eriksson et al, 2012;, which may lead to an advantage in describing fictional false beliefs.…”
Section: Sex Differencesmentioning
confidence: 99%